Risk factors, subsequent disease onset and prognostic impact of myocardial infarction and atrial fibrillation. (14th October 2021) - Camen, S; Csengeri, D; Geelhoed, B; Gianfagna, F; Soderberg, S; Kee, F; Blankenberg, S; Lochen, M L; Iacoviello, L; Tunstall-Pedoe, H; Joergensen, T; Salomaa, V; et al.
Abstract: Background: Myocardial infarction (MI) is a known risk factor for incident atrial fibrillation (AF), while AF frequently complicates acute MI. Although both diseases share common cardiovascular risk factors, the direction and strength of the association of the risk factors with disease onset, subsequent disease incidence and mortality are not completely understood. Purpose: Our goal was to define the temporal relationship of MI and AF and the association of cardiovascular risk factors with disease incidence in order to determine whether common clinical risk factors show different associations with incident MI or AF. We further aimed to investigate predictors of subsequent disease onset and the impact of subsequent disease diagnosis on mortality. Methods: In pooled multivariable Cox regression analyses we examined temporal relations of disease onset and identified predictors of MI, AF and subsequent all-cause mortality in 108, 363 individuals (median age 46.0 years, 48.2% men) free of MI and AF at baseline from six European population-based cohorts. Results: Over a maximum follow-up of 10.0 years 3558 (3.3%) individuals were diagnosed exclusively with MI, 1922 (1.8%) with AF but no MI, and 491 (0.5%) individuals developed both MI and AF. Association of male sex, systolic blood pressure, antihypertensive treatment and diabetes mellitus appeared to be stronger with incident MI than with AF, whereas increasing age and body mass index showed a higher risk for incident AF. Total cholesterol and daily smoking were significantly related to incident MI but not AF. The combined population attributable fraction of the cardiovascular risk factors was over 70% for incident MI, whereas it was only about one quarter for incident AF. Subsequent MI after incident AF (hazard ratio1.68, 95% CI 1.03–2.74) and subsequent AF after MI (hazard ratio 1.75, 95% CI 1.31–2.34) both significantly increased overall mortality risk. Conclusions: Subsequent diagnosis of MI and AF was associated with a significant increase in mortality, irrespective of the first event. We found different associations of common cardiovascular risk factors with incident MI and AF indicating distinct pathophysiological pathways in disease development. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 research and innovation programme (grant agreement No 847770, AFFECT-EU) European Union's Horizon 2020 research and innovation programme (grant agreement No 648131)